Analisis Proksimat Pada Bolu Kukus Dari Tepung Biji Durian - Elissandra Bange; Irwan Said; Nurhaeni (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Steamed sponge cake is a popular traditional snack widely enjoyed by the public. Generally, steamed sponge cake is made from wheat flour, which contains high carbohydrate levels. In this food product, the high carbohydrate content leads to rapid carbohydrate digestion, causing an increase in blood sugar levels, which is not beneficial for health. Therefore, this research formulated durian seed flour and cornstarch in a 50:50 ratio, which was the best formulation from previous organoleptic tests. Durian seeds were processed into durian seed flour, which has a highly beneficial nutritional content for health. The objectives of this study were to determine the carbohydrate, protein, and fat content and to utilize the research results as a learning medium in the form of a poster. In this study, three treatment repetitions were conducted for each test under the same conditions. Carbohydrate content was determined using the UV-VIS spectrophotometry method at a wavelength of 460 nm, protein content was determined using the micro-Kjeldahl method, and fat content was determined using the Soxhlet extraction method. The results obtained in this study showed that the proximate nutritional content of the steamed sponge cake was 44.0102% carbohydrate, 28% protein, and 23.01% fat. With a sufficiently high fiber content, the resulting glycemic index can be categorized as low, thus it can be used to meet the needs of individuals with DMT-2.